Neuronal representation of bimanual arm motor imagery in the motor cortex of a tetraplegia human, a pilot study - Lai, Dongrong; Wan, Zijun; Lin, Jiafan; Pan, Li; Ren, Feixiao; Zhu, Junming; Zhang, Jianmin; Wang, Yueming; Hao, Yaoyao; Xu, Kedi (Frontiers in Neuroscience, 2023)
Introduction How the human brain coordinates bimanual movements is not well-established. Methods Here, we recorded neural signals from a paralyzed individual’s left motor cortex during both unimanual and bimanual motor imagery tasks and quantified the representational interaction between arms by analyzing the tuning parameters of each neuron. Results We found a similar proportion of neurons preferring each arm during unimanual movements, however, when switching to bimanual movements, the proportion of contralateral preference increased to 71.8%, indicating contralateral lateralization. We also observed a decorrelation process for each arm’s representation across the unimanual and bimanual tasks. We further confined that these changes in bilateral relationships are mainly caused by the alteration of tuning parameters, such as the increased bilateral preferred direction (PD) shifts and the significant suppression in bilateral modulation depths (MDs), especially the ipsilateral side. Discussion These results contribute to the knowledge of bimanual coordination and thus the design of cutting-edge bimanual brain-computer interfaces.